Adipose-only sentinel lymph nodes: a finding during the adaptation of a sentinel lymph node mapping algorithm with indocyanine green in women with endometrial cancer. (7th January 2019) - Harold, J A; Uyar, D; Rader, J S; Bishop, E; Nugent, M; Simpson, P; Bradley, W H
Abstract : Objective: To identify factors that affect successful adaptation of sentinel lymph node mapping and those that lead to unintended adipose-only sentinel lymph node identification. Methods: Surgical and pathological data were prospectively collected on patients with endometrial cancer who underwent sentinel lymph node mapping with indocyanine green with or without pelvic and/or para-aortic lymph node dissection between November 2013 and April 2017. All mapping cases were performed with the robotic system. Adipose-only specimens were defined as a sentinel lymph node without a pathologically identified lymph node after ultrastaging. Results: A total of 202 patients were included: 83% had endometrioid pathology, 12% serous, 3% carcinosarcoma, and 2% clear cell, with mixed pathology noted in 2%. The bilateral sentinel lymph node detection rate was 66%, and the rate of mapping at least a unilateral sentinel lymph node was 86%. Neither the bilateral nor the unilateral sentinel lymph node mapping rate changed with increased surgeon experience. The rate of adipose-only sentinel lymph node identification was more frequent when comparing the first 10 cases (37%), cases 11 – 30 (28%), and > 30 cases (9%) (P = 0.006). Body mass index > 30 kg/m 2, uterine fibroids, The International Federation of Gynecology and Obstetrics (FIGO) grade, and histology were not found to have a statistically significant impact on either sentinel lymph node identification or adipose-only sentinel lymph node identification. Adipose-only sentinel lymph nodes were more likely with increased time from cervical injection to identification of the sentinel lymph node in the right hemipelvis. The median range was 28 min (14–73) for true sentinel lymph node identification vs 33 min (23–74) for adipose-only sentinel lymph node identification (P = 0.02). Conclusion: Patient and surgeon factors did not impact the identification of sentinel lymph nodes over time. Adipose-only sentinel lymph nodes were more frequently identified in the initial cases and represent a potential complication to adapting sentinel lymph node biopsy without lymphadenectomy. The increase in adipose-only sentinel lymph node identification that was associated with time from cervical injection may represent delayed or disrupted uptake of indocyanine green.